Adsorption of atmospheric gas molecules (NH3, H2S, CO, H2, CH4, NO, NO2, C6H6 and C3H6O) on two-dimensional polyimide with hydrogen bonding: a first-principles study. (8th March 2021) - Yu, Sujing; Zhang, Dongzhi; Pan, Wenjing; Zeng, Jingbin
Abstract : In this study, we investigated the effects of hydrogen bond acceptors on the surface of two-dimensional polyimide towards NH3, H2 S, CO, H2, CH4, NO, NO2, C6 H6 and C3 H6 O gas molecules through first-principles study based on density functional theory. Abstract : Herein, we investigated the effects of hydrogen bond acceptors on the surface of two-dimensional (2D) polyimide (PI) towards NH3, H2 S, CO, H2, CH4, NO, NO2, C6 H6 and C3 H6 O gas molecules through first-principles calculations based on density functional theory (DFT). The most stable adsorption configurations are proposed by simulating the adsorption behavior of gas molecules at three 2D PI positions (1-2DPI, 2-2DPI, and 3-2DPI) with different numbers of hydrogen bonds, and the parameters including adsorption energy, charge transfer, electron density, density of states (DOS), recovery time and frontier molecular orbitals were calculated. The simulation results indicate that the absolute values of adsorption energy of 2DPI-NH3, 2DPI-H2 S and 2DPI-CO configurations are greater than 0.8 eV, which can be regarded as chemisorption, while those of the 2DPI-H2, 2DPI-CH4, 2DPI-NO, 2DPI-NO2, 2DPI-C6 H6 and 2DPI-C3 H6 O are all less than 0.6 eV, which can be considered as physisorption. Interestingly, the existence of intermolecular hydrogen bonds significantly improves the adsorption capacity of 1-2DPI and 2-2DPI systems compared with the 3-2DPI system. Moreover, the DOS diagram demonstrates that these gas molecules exhibit a different influence on the electronic properties of the 2DPI substrate. It is worth noting that the electronic properties of 2DPI can be effectively changed after the adsorption of NH3, H2 S and CO, and 2-2DPI is the best position for gas adsorption. Our results indicate that the 2DPI monolayer with 2D structure and hydrogen bonds may be a good candidate for the detection of NH3, H2 S and CO, which opens up new prospects to design and research gas sensor applications.